Pengembangan Sistem Monitoring Kondisi Air Untuk Budidaya Lobster Air Tawar menggunakan Sensor IOT dan WEB - Awang Medidat; opiyan Apandi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Crawfish farmers carry out the process of monitoring water quality which is still done manually by dipping temperature gauges, acidity gauges and oxygen level gauges into the cultivation pond once a day every day. This method of manual monitoring can have quite a fatal impact on crawfish seedlings because it can disturb the lobsters themselves so that they can cause crop failure if they are not careful in the process of taking water samples. The solution to this problem is how to develop a water monitoring process without repeatedly dipping the tool into the aquaculture pond. In this research, a special tool is designed that can measure temperature, acidity (pH) and oxygen levels in the water which is installed into the aquaculture pond by utilizing IoT technology and designing a web-based application with the waterfall method which will then be integrated with this special tool to read the measurement results from the tool are used to monitor water quality in freshwater crawfish cultivation ponds without having to dip your hands every day